Problems of employment in Russian regions with excess labor force: Situation in services industry - B. Nagoev, Alim (2020)
The article presents an overview of services industries development in the most problematic regions of the Russian Federation. The assumption that the development of services in many regions will help stabilizing one of the most socially acute segments of the economy - the labor market, has been substantiated. The socio-economic problems affecting the world of work today are the result of an ill-conceived management policy in this area. The destruction of production ties, the privatization of large production plants and their unprofessional management led to a decrease in demand for labor and an increase in unemployment. The local authorities are still unable to solve the problem of unemployment in some regions of the Russian Federation. Moreover, many social groups situation is becoming more complicated from year to year. This can have painful consequences, especially in the Russian regions. Along with improving the situation on the labor market, it is noted that there is a need to ease the requirements of employers for job-seekers.